"Svolazza" Lucifero come le anime dei morti ? ("Inferno", XXXIV, 46-52) - Marco Chiariglione (Parole Rubate, 2014)
This article aims to demonstrate the relationship between Dante's comparison of Lucifer's flapping wings to those of a bat and the movement of the souls of the dead in classical antiquity. It will explore some textual references from heterogeneous and distant traditions, from the Greek and Roman classics, the Fathers of the Church, the medieval bestiaries and encyclopedias, to Dante himself.